Phổ tra tỉ mỉ chì kẽm Cao Sơn - Mường Khương - Trương, Văn Xuân (2011)
Tác giả: Trương Văn Xuân; Nghiêm Thái Thịnh, KS; Nguyễn Văn Phục, KS; Nguyễn Văn Hải, KS; Trần Đức Bảo -- Từ khóa: Quặng; Chì; Kẽm; Khoáng vật; Canxiterit; SnO2